문헌정보학 분야 정보격차 연구동향 분석 - 강인서; 김혜진; Kang, In-Seo; Kim, Hea-Jin (Chŏngbo Kwalli Hakhoechi, 2020)
This study aimed to analyze research trends of 'digital divide' in Library and Information Science. To this end, we coded research subjects with 11 subcategories, and research objectives with 4 subcategories, and research methods with 4 subcategories, and constructed keyword networks to which a pathfinder algorithm was applied. As a result of the analysis, 79.5% of studies are on the disabled, multicultural families, and the elderly among information vulnerable groups, and it was found to be concentrated in specific groups. In addition, digital divide related studies have been actively conducted for the purpose of resolving information vulnerabilities such as people with disabilities. We also found that these studies focused on verifying the effectiveness by designing and applying treatments such as informatization education, information utilization, and reading programs. Lastly, the most frequently used research method in the digital divide was found to use case studies or questionnaires simultaneously with literature research. 본 연구는 문헌정보학에서 다뤄지는 정보격차 연구동향을 분석하기 위해서 문헌정보학관련 4개 학술지에서 발행한 195편의 논문을 수집하고, 해당 문헌을 대상으로 연구대상(11개 하위 범주), 연구목적(4개 하위 범주), 연구방법(4개 하위 범주)로 코딩하였다. 이것을 저자 키워드와 함께 패스파인더 알고리즘을 적용한 키워드 네트워크를 구축하여 분석을 진행하였다. 분석 결과, 정보취약계층(연구대상) 중 장애인, 다문화가정, 고령자에 대한 연구가 79.5%로 특정 계층에 집중되어있는 것으로 나타났다. 그리고 정보격차, 장애인, 공공도서관을 중심으로, 다문화, 고령자 등에 대한 정보취약 실태와 해소방안을 목적으로 활발히 연구가 진행되었으나, 정보취약 해소효과, 정보취약의 영향요인을 목적으로 한 연구는 고령자, 독서치료, 정보화교육, 정보활용, 독서프로그램을 구안하고 적용하여 효과를 검증하는 연구에 국한되어 있었다. 마지막으로 정보격차에서 가장 많이 활용되는 연구방법은 문헌연구와 함께 사례연구 또는 설문조사를 동시에 이용하는 것으로 나타났다.